System of controlling temperature conditions by drum-type rotary furnace in obtaining uranium oxides; Bulletin of the Tomsk Polytechnic University; Vol. 310, № 1 - Brendakov V. N.; Dementiev Yu. N. Yuriy Nikolaevich; Kladiev S. N. Sergey Nikolaevich; Pishchulin V. P. (Power engineering, 2007)
Заглавие с титульного листа